Magnetic resonance imaging of gas dynamics in the freeboard of fixed beds and bubbling fluidized beds. (22nd June 2016) - Boyce, C.M.; Rice, N.P.; Davidson, J.F.; Sederman, A.J.; Dennis, J.S.; Holland, D.J.
Abstract: Magnetic resonance imaging (MRI) was used to measure directly gas velocity and gas velocity distribution in the freeboard region of a fluidized bed (52 mm dia.) under bubbling fluidisation and just below minimum fluidisation. The bed consisted of poppy seed particles 1.1 mm in diameter and was fluidized using SF6 gas at 7.5 barg for MRI purposes. In the system, bubbles approximately 20 mm in diameter rose through the centre of the bed. In the case of bubbling fluidisation, time-averaged velocity maps at different vertical positions in the freeboard showed downward moving gas in the centre of the bed and upward moving gas near the walls for this particular bed. However, below minimum fluidisation conditions, the profiles of gas velocity in the freeboard were flat, with respect to the radial dimension, with minor and random spatial variance, indicating that the profiles observed during bubbling arose from bubble breakthrough. The reasons for these observed patterns of flow are discussed. Highlights: MRI used to measure of gas velocity in the freeboard of a fluidized bed Dramatically different gas flow patterns observed in bubbling and fixed beds Findings consistent with toroidal vortex theory for gas flow in freeboard